The Effect of Stem Cutting Time on the Growth and Yield of Lowland Rice on the Organic-Based SALIBU System - Najoan, Jemmy; Paulus, MS, Jeanne M.; Demmassabu, Langimanapa Sofia (JURNAL BIOS LOGOS, 2025)
Innovation in organic-based rice cultivation technology is needed to overcome the food crisis. One method is the SALIBU (single planting, multiple harvests) system, which requires precise control of rice stem cutting height. This study aims to examine the growth and production of lowland rice in response to rice stem cutting height using the SALIBU method. Field research was conducted for six months (April-October 2024) in Taratara Dua Village, Tomohon City. The materials used included Inpari 32 rice seeds, straw compost, liquid organic fertiliser, and Phonska NPK fertiliser. This study used a Randomised Block Design (RBD) with four stem cutting time treatments: 0, 3, 6, and 9 days after harvest, each with three replications. Observed variables included plant height, number of productive tillers, number of full and empty grains per panicle, and harvest yield. The results showed that stem cutting time significantly affected plant height, number of productive tillers, number of full grains, and harvested dry grain yield (GKP). However, there was no significant effect on the number of empty grains. The most effective time for cutting stems is 0 days after harvest (at harvest time).